OLD AND NEW FORMS OF ARTISTIC ENGAGEMENT IN A CULTURE OF RESISTANCE - Gudović, Zoran (Politeia, 2023)
Using the ethno-methodological theoretical paradigm and the historical method, the author comes to the conclusion that culture, politics and the artistic atmosphere that enriches space form an indivisible structure of events and phenomenological perception of the culture of resistance in modern society. The culture of civil resistance present in art is inseparable from political movements and opposition to repression. Political protests have also become a form of performance that the author seeks to observe from a broader context of street culture in the theoretical perception of the epistemology of space. This way, the tendency and ability to see the meaning and spirit of various manifestations is allowed to come forth. Socio-cultural preconceptions of various art forms and manifestations as well as their historical, political, and ideological conditioning in the global environment and (post) globalism are all explored. As the main research subject, the author takes caricature and art of aphorism, perceived as traditional forms of resistance, and performance, due to its visual and expressionist-based message as a relatively new artistic practice and a more effective form of civil resistance. By determining the meaning of phenomena using linguistic and visual representations, the author notices the political nature of their expression. In this paper, the author strives to break the ‘modern dogma’ by which politics and art are in an inherent conflicting relationship. Therefore, the basic thesis of the text is the author’s effort to bring the goals of politics and art conceptually closer through the basic proclamation of human freedom. The foundation of freedom and creative choice constitute their common and fundamental value. Performance establishes a rational compromise in which the government and opposition groups believe in the democratic potential of their role, pacifying the space in the new circumstances. Ideological fervor and propaganda goals make an unfortunately thin line between the cultured and the uncultured.
Keywords: art; civic resistance; politics; performance; urban space